2019
DOI: 10.1016/j.jphotobiol.2019.111561
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp stem cells therapy overcome photoreceptor cell death and protects the retina in a rat model of sodium iodate-induced retinal degeneration

Abstract: Blindness and vision loss contribute to irreversible retinal degeneration, and cellular therapy for retinal cell replacement has the potential to treat individuals who have lost light sensitive photoreceptors in the retina. Retinal cells are well characterized in function, and are a subject of interest in cellular replacement therapy of photoreceptors and the retinal pigment epithelium. However, retinal cell transplantation is limited by various factors, including the choice of potential stem cell source that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Numerous studies have revealed that DPSCs could migrate to the lesion site, which accelerates tissue repair and regeneration [16,17]. In addition, DPSCs present easy access, low-risk immune rejection and fewer ethical issues; hence, they can be used as ideal gene vehicles with wide application prospects [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that DPSCs could migrate to the lesion site, which accelerates tissue repair and regeneration [16,17]. In addition, DPSCs present easy access, low-risk immune rejection and fewer ethical issues; hence, they can be used as ideal gene vehicles with wide application prospects [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that cell death may occur by induction of oxidative stress (Sachdeva et al, 2014). Previous study have shown that it can react specifically with this cell type in many animal species [e.g., and rabbits (Shen et al, 2010), rats (Alsaeedi et al, 2019), and sheep (Nilsson et al, 1977)]. When added into the ARPE-19 cell culture, a loss of epithelial cell morphology could be observed within 24 h (Figure 1).…”
Section: Discussionmentioning
confidence: 95%
“…Mesenchymal stem cells (MSCs) has emerged as a suitable choice for replacement of retinal cells, particularly the photoreceptors (Leow et al 2015) and retinal pigmented epithelial cells (Alsaeedi et al 2019), which are highly affected in AMD progression (Bhutto & Lutty 2012). Despite many reported methods to generate photoreceptors in vitro or direct cell transplantations (Ding et al 2017), achievement of treatment outcomes remained far from ideal.…”
Section: Resultsmentioning
confidence: 99%